What Is the magnitude and long-term economic cost of care of the British military Afghanistan amputee cohort? - Edwards,DS; Phillip,RD; Bosanquet,N; Bull,AMJ; Clasper,JC (Clinical Orthopaedics and Related Research, 2015)
BackgroundPersonal protection equipment, improved early medical care, and rapid extraction of the casualty have resulted in more injured service members who served in Afghanistan surviving after severe military trauma. Many of those who survive the initial trauma are faced with complex wounds such as multiple amputations. Although costs of care can be high, they have not been well quantified before. This is required to budget for the needs of the injured beyond their service in the armed forces.Question/purposesThe purposes of this study were (1) to quantify and describe the extent and nature of traumatic amputations of British service personnel from Afghanistan; and (2) to calculate an estimate of the projected long-term cost of this cohort.MethodsA four-stage methodology was used: (1) systematic literature search of previous studies of amputee care cost; (2) retrospective analysis of the UK Joint Theatre Trauma and prosthetic database; (3) Markov economic algorithm for healthcare cost and sensitivity analysis of results; and (4) statistical cost comparison between our cohort and the identified literature.ResultsFrom 2003 to 2014, 265 casualties sustained 416 amputations. The average number of limbs lost per casualty was 1.6. The most common type of amputation was a transfemoral amputation (153 patients); the next most common amputation type was unilateral transtibial (143 patients). Using a Markov model of healthcare economics, it is estimated that the total 40-year cost of the UK Afghanistan lower limb amputee cohort is £288 million (USD 444 million); this figure estimates cost of trauma care, rehabilitation, and prosthetic costs. A sensitivity analysis on our model demonstrated a potential ± 6.19% variation in costs.ConclusionsThe conflict in Afghanistan resulted in high numbers of complex injuries. Our findings suggest that a long-term facility to budget for veterans’ health care is necessary.